Prolonged standing and work fatigue on sales promotion girl workers at the Kubu Raya Regency Shopping Center - Sunarsieh, Sunarsieh; Adib, Moh (Intelektual Pustaka Media Utama, 2023)
Standing positions are used for almost all jobs, including sales promotion girl or SPG workers. Standing in working positions for long periods can cause work fatigue. This study aimed to analyze the relationship between the length of work in a standing position and the work fatigue of SPG workers. This research is a cross-sectional study. Fatigue data collection was carried out by interviews using the industrial fatigue research committee (IFRC) questionnaire. Data on the length of work in a standing position are obtained by interview and observation. Based on the results of the study, as many as 66.7% of workers at SPG in the shopping center of Kubu Raya Regency, Indonesia in one day work in a standing position for eight hours, and 33.3% work in a standing position for >8 hours. The average level of work fatigue at the beginning of work is 49.38, and after work is 52.95, with the results of statistical analysis showing a p-value of 0.000, meaning that there is a significant relationship between long-standing position and work fatigue. There is a need for supervision and monitoring related to the work safety system regularly carried out by the manager of the shopping center, which is also supervised by the Ministry of Health and the Ministry of Manpower.